Crescita economica e coesione sociale nelle democrazie avanzate Un divorzio inevitabile? - Trigilia, Carlo (Lectio Magistralis, 2017)
After the Second World War, the economies of advanced Countries have long been characterized by inclusive economic growth. In recent decades, on the other hand, there has been a steady increase in inequalities and a worsening for low-income social groups. What is the possibility of rebuilding a more inclusive development like that of the post-war three decades? Is it a viable road? And under what conditions? Or should we instead speculate that divorce is inevitable between economic growth and social cohesion in advanced democracies? There is no sure answer to this question, but it can be a good exercise, especially for those who believe that inclusive development is an essential component of the quality and stability of democracies, asking themselves under what conditions we can try to pursue this goal. The path proposed in this text focuses, in a comparative key, on the significant differences in the forms of economic and social regulation between the various advanced democracies that are reflected in more or less inclusive development paths and models of capitalism. Why have some countries managed to better defend the conditions for inclusive development over the past three decades? Through which economic and social regulatory choices? Moreover, another overlooked question is worth asking. How has politics created consensus around these choices and made them possible, while in other contexts it has supported growth accompanied by greater inequalities? What is certain is that giving up the goal of finding a more satisfactory balance between economic growth and social cohesion not only jeopardizes economic development, but also weakens and impoverishes democratic institutions.